An improved region—time—length algorithm applied to the 1999 Chi-Chi, Taiwan earthquake - Chen, Chien-Chih; Wu, Yi-Xuan (Geophysical journal international, 2006)
By means of the region—time—length (RTL) algorithm, which is widely used for investigating the precursory seismicity changes in China, Italy, Japan, Russia and Turkey, we examine the precursory seismic activity occurred prior to the 1999, Mw= 7.6, Chi-Chi earthquake around its epicentre. Based on our calculation of the RTL values, the epicentral area has been found to strongly exhibit the signature of anomalous activity, associated with the seismic quiescence and activation, before the main shock. Also proposed in this study is a helpful method for determining two important parameters used in the RTL analysis, the characteristic time and distance. Such method will largely reduce the ambiguity in the original RTL algorithm.